Synergistic Synbiotic-Containing Lactiplantibacillus plantarum and Fructo-Oligosaccharide Alleviate the Allergenicity of Mice Induced by Soy Protein - Jing Bai; Qian Zeng; Wen Den; Liheng Huang; Zhihua Wu; Xin Li; Ping Tong; Hongbing Chen; Anshu Yang (Foods)
Prebiotics and probiotics have key roles in the intervention and treatment of food allergies. This study assesses the effect of Lactiplantibacillus plantarum synergistic fructo-oligosaccharide (Lp–FOS) intervention using an allergic mouse model induced by soy protein. The results showed that Lp synergistic FOS significantly decreased clinical allergy scores, inhibited specific antibodies (IgE, IgG, and IgG1), IL-4, IL-6, and IL-17A levels, and increased IFN-γ and IL-10 levels. Meanwhile, flow cytometry showed that Lp–FOS intervention inhibited the percentage of dendritic cell (DC) subsets in splenocytes and increased the Th1/Th2 and Treg/Th17 ratios. Furthermore, Lp–FOS intervention upregulated the mRNA levels of T-bet and Foxp3 and downregulated the mRNA levels of GATA3. Finally, non-targeted metabolomic analysis showed that Lp–FOS improved serum metabolic disorders caused by food allergies through regulating glycine, serine, and threonine metabolism, butanoate metabolism, glyoxylate and dicarboxylate metabolism, the biosynthesis of cofactors, and glycerophospholipid metabolism. These data showed that the combination formulation Lp–FOS could be a promising adjuvant treatment for food allergies.